Development of a carboplatin derivative conjugated with a collagen-like triple-helical peptide. (7th February 2018) - Masuda, Ryo; Hayashi, Risa; Nose, Hiroshi; Taguchi, Akihiro; Hayashi, Yoshio; Yasui, Hiroyuki; Koide, Takaki
Aim: The development of a platinum anticancer agent that has improved efficacy by efficient delivery to a tumor and that suppresses side effects has been investigated. Arginine-rich triple-helical peptides are promising drug carriers because of their stability in body fluids and cell-penetrating activity.Results: We synthesized a carboplatin derivative conjugated with an arginine-rich triple-helical peptide. This derivative released platinum under acidic conditions or in the presence Cl - ions. Administration of this derivative to P388 tumor-bearing mice showed comparable survival rates to twice the dose of carboplatin, which was attributed to a longer mean residence time by pharmacokinetics analysis.Conclusion: The collagen-like triple-helical peptide was an efficient carrier of a platinum anticancer agent because of a modification to its pharmacokinetic profile. Graphical abstract: